PENGARUH PERBEDAAN JENIS ASAM TERHADAP KADAR ALKALOID TOTAL DAUN BANDOTAN (Ageratum conyzoides, L.) - Verawati verawati (Fakultas Farmasi Universitas 17 Agustus 1945 Jakarta, 2017)
The research about estimating amount of total alkaloid of the leaves bandotan (Ageratum conyzoides, L.) by varying the type of acid in the extraction process of alkaloids. Alkaloid from bandotan dried leaf powder was extracted by using 3 types of acids are hydrochloric acid (HCl), phosphoric acid (H3PO4), acetic acid (CH3COOH). Extract qualitatively analyzed using Thin Layer Chromatography (TLC) using a dye dragendorf. At alkaloid extracted with HCl showed the number of stains sharper than the two other extracts. Alkaloid assay gravimetric done and obtained the number of total alkaloids significantly different among the three (P <0.05) which is the largest number in the alkaloid extracted with hydrochloric acid (HCl) of 45.9598% w/w, followed alkaloid extracted with phosphate (H3PO4) 11.2016% w/w, and alkaloid extracted with acetic acid (CH3COOH) 1.9536% w/w.